A review of the landscape of agroecology policies towards transforming food systems in Sub-Saharan Africa - Kevin Okoth Ouko; Cherine Lando Yugi; Modock Odiwuor Oketch; Jimmy Brian Mboya; Robert John Ogola; Mavindu Muthoka; Dick Chune Midamba (Cogent Social Sciences)
Sustainability serves as a normative principle in the context of food policy but also represents a hotly debated arena. Ongoing crises in contemporary agriculture suggest that the current model of food production may not be sustainable in the long run to guarantee global food security. Advocacy for more comprehensive and sustainable models has increased because of the pressing need to improve agriculture, particularly in Africa. Thus, the status quo cannot be maintained. Agroecology-based food system transformation has received increased attention from social movements, academics, researchers and policymakers. In many countries around the world, agroecology is becoming increasingly popular as a transformative movement. However, it receives little attention in global agricultural research and development plans, particularly in sub-Saharan Africa (SSA). Scaling up agroecological outputs requires amplification. This research explores amplification dynamics through a literature review, providing insights into SSA’s emerging agroecology policy landscape while drawing on Cuba’s experiences. Adopting agroecological practices contributes to accomplishing Sustainable Development Goal (SDG) number 2 of the United Nations while providing solutions to food insecurity in SSA. The findings suggest that while agroecology is becoming more common and well-known in SSA, its presence is still modest, and there is little policy support for its expansion. Agroecology’s holistic approach with an ecological foundation is yet to take a foothold in SSA’s food system policy arena. Several policy recommendations have been suggested in this review paper to support agroecology research and policy discourse in SSA and its role in transforming agri-food systems.